EgoSENSE: A Framework for Context-Aware Mobile Applications Development - Milic, E. M.; Stojanovic, D. (Engineering, Technology & Applied Science Research, 2017)
This paper presents a context-aware mobile framework (or middleware), intended to support the implementation of context-aware mobile services. The overview of basic concepts, architecture and components of context-aware mobile framework is given. The mobile framework provide acquisition and management of context, where raw data sensed from physical (hardware) sensors and virtual (software) sensors are combined, processed and analyzed to provide high-level context and situation of the user to the mobile context-aware applications in near real-time. Using demo mobile health application, its most important components and functions, such as these supposed to detect urgent or alarming health conditions of a mobile user and to initiate appropriate actions demonstrated.